On Fingerprinting of Public Malware Analysis Services. (7th December 2019) - Botas, Alvaro; Rodríguez, Ricardo J; Matellan, Vicente; Garcia, Juan F; Trobajo, M T; Carriegos, Miguel V
Abstract: Automatic public malware analysis services (PMAS, e.g. VirusTotal, Jotti or ClamAV, to name a few) provide controlled, isolated and virtual environments to analyse malicious software ( malware ) samples. Unfortunately, malware is currently incorporating techniques to recognize execution onto a virtual or sandbox environment; when an analysis environment is detected, malware behaves as a benign application or even shows no activity. In this work, we present an empirical study and characterization of automatic PMAS, considering 26 different services. We also show a set of features that allow to easily fingerprint these services as analysis environments; the lower the unlikeability of these features, the easier for us (and thus for malware) to fingerprint the analysis service they belong to. Finally, we propose a method for these analysis services to counter or at least mitigate our proposal.